THE EFFECT OF ORGANIZATIONAL CLIMATE AND COMPENSATION ON JOB SATISFACTION OF ADMINISTRATIVE EMPLOYEES UIN AR-RANIRY BANDA ACEH - Yulindawati Yulindawati (Universitas Islam Negeri Ar-Raniry, 2021)
The purpose of this study was to determine the compensation of the organizational climate and job satisfaction partially or simultaneously to the administration of employee performance UIN Ar-Raniry Banda Aceh. The population in this study was done by using Proportional Stratified Random Sampling by the number of employees 162 people made in the research sample. The analysis methods used were data instrument tests which are data validity as well .The results showed a positive relationship between organizational climate variables and compensation effect on job satisfaction UIN Ar-Raniry Administration Banda Aceh.